2017
DOI: 10.14814/phy2.13078
|View full text |Cite
|
Sign up to set email alerts
|

Tool selection and the ventral‐dorsal organization of tool‐related knowledge

Abstract: Tool selection is a cognitive process necessary for tool use, and may rely on distinct knowledge under different conditions. This fMRI experiment was designed to identify neural substrates mediating tool selection under different conditions. Participants performed a picture‐matching task that presented a recipient object and an action‐goal, and required the selection of the best tool object from among four candidates. Some trials allowed selection of the prototypical tool, whereas others forced selection of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Our results demonstrated that the pathological BPO use was associated with anterior lesions in inferior frontal as well as middle temporal regions extending to the temporal pole. Therefore, as hypothesized, BPO errors are mainly induced by anterior lesions of a left fronto-temporal network, which is assumed to be relevant for the retrieval and combination of semantic knowledge about tools and their use ( Binder et al, 2009 ; Goldenberg and Spatt, 2009 ; Hogrefe et al, 2017 ; Tobia and Madan, 2017 ). Further, temporal pole lesions are related to semantic processing deficits ( Hodges et al, 1992 ; McClelland and Rogers, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrated that the pathological BPO use was associated with anterior lesions in inferior frontal as well as middle temporal regions extending to the temporal pole. Therefore, as hypothesized, BPO errors are mainly induced by anterior lesions of a left fronto-temporal network, which is assumed to be relevant for the retrieval and combination of semantic knowledge about tools and their use ( Binder et al, 2009 ; Goldenberg and Spatt, 2009 ; Hogrefe et al, 2017 ; Tobia and Madan, 2017 ). Further, temporal pole lesions are related to semantic processing deficits ( Hodges et al, 1992 ; McClelland and Rogers, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to tool use actions, inferior frontal and temporal regions have been reported to contribute to semantic processing ( Hodges et al, 2000 ; Hogrefe et al, 2017 ; Jefferies, 2013 ; Patterson et al, 2007 ) or related functional grasping movements ( Randerath et al, 2010 ). Conversely, dorsal stream structures, including the parietal cortex, have frequently been associated with processes involving how an object or body part can be manipulated ( Almeida et al, 2010 ; Buxbaum and Saffran, 2002 ; Goodale and Milner, 1992 ; Johnson-Frey, 2004 ; Tobia and Madan, 2017 ). These functional attributions may fit the idea of two major networks supporting pantomime of object use: one contributing predominantly to the communicative nature of pantomiming, and the other one supporting predominantly motor cognitive aspects such as the spatial configuration of the body, hands and their movements.…”
Section: Introductionmentioning
confidence: 99%
“…More recent evidence indicates, however, that skilled use actions are mediated by relatively more ventral regions (the “ventro-dorsal stream”), are strongly left-lateralized, and are consciously accessible (e.g., Ishibashi et al, 2016; M. Martin et al, 2016; Tobia and Madan, 2017; see Binkofski and Buxbaum, 2013; for discussion). One possibility is that the relatively low probability of detection of action similarity results from a cognitive bias to rely upon “taxonomic” features such as function and appearance as well as typical “thematic” features such as location (e.g., “kitchen”) and temporal events (e.g., “birthday”) in categorization tasks (see Mirman et al, 2017 for review).…”
Section: Discussionmentioning
confidence: 99%
“…Several more specific motor dimensions may drive the BOI effects observed in lexical-semantic processing. In particular, there are specific aspects of object manipulation that have primarily been explored in the cognitive neuroscience, neuropsychology, and/or object recognition literatures, in which the stimuli are line drawings or photographs (e.g., Boronat et al, 2005;Garcea & Mahon, 2012;Guérard, Lagacé, & Brodeur, 2015;Madan, Chen, & Singhal, 2016;Madan, Ng, & Singhal, 2018;Salmon, Matheson, & McMullen, 2014;Salmon, McMullen, & Filliter, 2010;Tobia & Madan, 2017). In the present work we considered whether these specific dimensions are related to BOI and whether they also explain word recognition behavior.…”
Section: Candidate Motor Dimensionsmentioning
confidence: 99%